Brain Ischemia as a Prelude to Alzheimer's Disease - Pluta, Ryszard; Januszewski, Sławomir; Czuczwar, Stanisław J. (Frontiers in Aging Neuroscience, 2021)
Transient ischemic brain injury causes massive neuronal death in the hippocampus of both humans and animals. This was accompanied by progressive atrophy of the hippocampus, brain cortex, and white matter lesions. Furthermore, it has been noted that neurodegenerative processes after an episode of ischemia-reperfusion in the brain can continue well-beyond the acute stage. Rarefaction of white matter was significantly increased in animals at 2 years following ischemia. Some rats that survived 2 years after ischemia developed severe brain atrophy with dementia. The profile of post-ischemic brain neurodegeneration shares a commonality with neurodegeneration in Alzheimer's disease. Furthermore, post-ischemic brain injury is associated with the deposition of folding proteins, such as amyloid and tau protein, in the intracellular and extracellular space. Recent studies on post-ischemic brain neurodegeneration have revealed the dysregulation of Alzheimer's disease-associated genes such as amyloid protein precursor, α-secretase, β-secretase, presenilin 1, presenilin 2, and tau protein. The latest data demonstrate that Alzheimer's disease-related proteins and their genes play a key role in the development of post-ischemic brain neurodegeneration with full-blown dementia in disease types such as Alzheimer's. Ongoing interest in the study of brain ischemia has provided evidence showing that ischemia may be involved in the development of the genotype and phenotype of Alzheimer's disease, suggesting that brain ischemia can be considered as a useful model for understanding the mechanisms responsible for the initiation of Alzheimer's disease.